Pengaruh Technology Support dan Online Marketing Strategy dengan Aplikasi Gojek Fitur Gofood Terhadap Peningkatan Pendapatan Usaha UMKM di Badung - I Gusti Ayu Mas Prihandani; I Kadek Donny Wishanesta; Ni Luh Indiani (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The development of the business world is inseparable from the role of a micro business, namely micro, small, and medium enterprises (MSMEs). MSMEs are one type of micro business that plays a very important role in improving and growing the community's economy. The role of micro, small, and medium enterprises (MSMEs) helps increase economic growth rates and is able to absorb the number of workers and the distribution of development results can increase so that it can be felt by the community. This research aims to analyze the influence of technology support and online marketing strategy simultaneously on increasing income from the Gilimanuk specialty betutu chicken culinary business. The number of samples used was 30 people, data collection used a questionnaire. The research object uses two independent variables, namely technology support and online marketing strategy, and one dependent variable, namely increasing income. The data analysis technique uses multiple linear regression analysis. Based on the research results, it is known that the technology support variable has a t count of 13.697 and a t table of 1.7, a significance value of 0.000. The online marketing strategy variable (X2) has a calculated t of 22.713, a t table value of 1.7, a significance value of 0.000. Meanwhile, technology support and online marketing strategy have an F-count of 468.899 with a sig of 0.000, this means that there is a significant influence simultaneously (simultaneously) from the influence of technology support and online marketing strategy simultaneously on increasing income.